Em jogo de memórias, os "caminhos" de João Maimona - Meloni, Otávio Henrique Rodrigues (2008)
This work has intention of mapping out a path for the solid work of João Maimona, analyzing their importance in the cultural scene of post-independence Angola. For this, directing our analysis to what we consider some points of strength of this poetic Angolan poet: a memory in its tracks, construction the landscape of the poem, constitution the poetic subject and depuration of language. We believe that his poetry is a spread in the letters of your country, either by working with the word poetic, as the social and literary themes recovered by the author. The poetry of João Maimona is a genuine display of events that is constantly formation.